2015
DOI: 10.1074/jbc.m115.645549
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Primes the NALP3 Inflammasome by Inhibiting Its Ubiquitination and Degradation Mediated by the SCFFBXL2 E3 Ligase

Abstract: Background: LPS increases NALP3 levels, but the mechanisms remain unknown. Results: LPS prolongs the lifespan of NALP3 protein by reducing E3 ligase (SCF FBXL2 )-mediated ubiquitination. Conclusion: Proinflammatory cytokine release is reduced by a small molecule that restores cellular SCF FBXL2 levels. Significance: We identified a novel pathway of inflammasome priming that may serve as a springboard for future translational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(151 citation statements)
references
References 26 publications
3
142
4
2
Order By: Relevance
“…Thus, Yan et al (40) reported that K48-linked ubiquitination negatively regulated NLRP3 inflammasome activity by promoting the degradation of NLRP3. This idea was supported by Han et al (41) and Song et al (15), although they identified different ubiquitinases as operative compared with those identified by Yan et al In addition, Py et al (14) showed that deubiquitination of both K63-and K48-linked polyubiquitin chains was required for NLRP3 inflammasome activation. A somewhat different view of the role of polyubiquitination in NLRP3 activation was suggested by Wei et al (42), who showed that the Yersinia-type III secretion effector YopM promoted K63-linked polyubiquitination and activation of NLRP3; thus, in this case, K63-linked polyubiquitination was shown to be a positive regulator of the NLRP3 inflammasome.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, Yan et al (40) reported that K48-linked ubiquitination negatively regulated NLRP3 inflammasome activity by promoting the degradation of NLRP3. This idea was supported by Han et al (41) and Song et al (15), although they identified different ubiquitinases as operative compared with those identified by Yan et al In addition, Py et al (14) showed that deubiquitination of both K63-and K48-linked polyubiquitin chains was required for NLRP3 inflammasome activation. A somewhat different view of the role of polyubiquitination in NLRP3 activation was suggested by Wei et al (42), who showed that the Yersinia-type III secretion effector YopM promoted K63-linked polyubiquitination and activation of NLRP3; thus, in this case, K63-linked polyubiquitination was shown to be a positive regulator of the NLRP3 inflammasome.…”
Section: Discussionsupporting
confidence: 65%
“…L'expression de l'E3 ligase SCF FBXO3 est induite lors du priming transcriptionnel. Elle réprime SCF FBXL2 par ubiquitination et dégrada-tion [36]. À noter qu'au cours du priming transcriptionnel, la pro-IL-1 est également ubiquitinée sur la lysine K133 par des enzymes qui restent cependant à identifier.…”
Section: Les Voies De Signalisation Qui Contrôlent L'assemblage De L'unclassified
“…LPS priming prolongs the lifespan of NLRP3 by inducing and activating the FBXL2 inhibitor FBXO3. 29 Of note, apart from its protein levels, the activity of NLRP3 is also subject to post-translational regulation by ubiquitination. It has recently been shown that the DUB BRCC3 profoundly promotes inflammasome activation by deubiquitinating NLRP3, whereas the level of BRCC3 does not correlate with the abundance of NLRP3 after LPS exposure, hinting that non-degradative K63-linked ubiquitination might obstruct NLRP3 inflammasome activation in resting macrophages.…”
Section: Inflammasome Signalingmentioning
confidence: 99%